2014
DOI: 10.1530/joe-13-0449
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of autophagic activation in the mouse uterus by estrogen and progesterone

Abstract: Autophagy is a major cellular catabolic pathway tightly associated with cell survival. The involvement of autophagy in the prolonged survival of blastocysts in the uterus is well established, and it was assumed that ovarian steroid hormones -progesterone (P 4 ) and estrogens -have important roles in the regulation of autophagy. However, information is scarce regarding whether these hormones regulate autophagy in certain hormoneresponsive cellular systems. In this study, we investigated the effects of estrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 39 publications
1
49
0
1
Order By: Relevance
“…The MTT results showed that MPA significantly inhibited the proliferation of parental but not PRCs (Figure 1A). Previous studies21 showed lower expression of PR in PRCs. We also found lower expression of PR in our system (Figure 1B).…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…The MTT results showed that MPA significantly inhibited the proliferation of parental but not PRCs (Figure 1A). Previous studies21 showed lower expression of PR in PRCs. We also found lower expression of PR in our system (Figure 1B).…”
Section: Resultsmentioning
confidence: 68%
“…Induction of progestin-resistant EC cell line was described previously 21. Briefly, Ishikawa cells were maintained in Dulbecco’s Modified Eagle’s Medium supplemented with 10% fetal bovine serum, and MPA (Sigma-Aldrich Co., St Louis, MO, USA) was added for 6 months.…”
Section: Methodsmentioning
confidence: 99%
“…These data suggest that estrogen could negatively regulate autophagy in OST. Autophagy inhibition by estrogen has also been observed in mouse uterus, rat cardiomyocytes and rat motor neurons [3234]. Conversely, estradiol was shown to increase autophagy mediated by serum deprivation in OB, suggesting that the pro- or anti-autophagy effects of estrogens are cell- and context-dependent [35].…”
Section: Discussionmentioning
confidence: 99%
“…Choi et al 15 explored whether hormones regulated autophagy in the mouse uterus and found that high levels of LC3-II, a marker of autophagic activity was detected in the uterus during the first 2 days of pregnancy, coinciding with the highest levels of estrogen (E 2) in the uterus and decreased at day 4 when P4 levels are higher. Incidentally, levels of P62, typically associated with reduced autophagy, also rise at day 4.…”
Section: 14mentioning
confidence: 99%